Potential application of fish scales as feedstock in thermochemical processes for the clean energy generation - Silva, Arthur Vinicius Sousa; Torquato, Lilian D. Moura [UNESP]; Cruz, Glauber (Elsevier, 2019)
The replacement of fossil fuels by renewable sources has been discussed globally, because fossil fuels account for a large portion of the pollutant emissions into the atmosphere. Several cities along the Brazilian coast produce a variety of fish types, generating a large amount of waste, including viscera and fish scales, which are already used in several industrial processes. However, these cities still face a large environmental problem, i.e., residue disposal from commercial establishments, e.g., fishmongers, which are often discarded in a disordered and/or unplanned manner in inappropriate places. Within this scenario, the energy utilization of an animal biomass supplied by a fishery in the city of São Luís was investigated, submitting samples to combustion (synthetic air) and pyrolysis (100% N2) processes for the bioenergy generation. Physicochemical properties from fish scales were evaluated by proximate and ultimate analyzes, scanning electron microscopy (SEM), energy dispersive spectroscopy (EDS), X-Ray diffraction (XRD), Fourier transform infrared spectroscopy (FTIR) and inductively coupled plasma - optical emission spectroscopy (ICP-OES). The thermal behavior of samples was evaluated by thermogravimetry/derivative thermogravimetry (TG/DTG), differential thermal analysis (DTA) and calorimetry (HHV/LHV). It was verified that the fish scales have carbon and oxygen the major elements, and insignificant amounts of sulfur and heavy metals (lead, copper, chromium, lithium, zinc). This material also presented a large amorphous region (89%), in addition to the presence of collagen fibers and hydroxyapatite crystals. The thermal and physicochemical characteristics of this material were evaluated and compare it to other biomasses already in use, predicting its use for the bioenergy generation.
Keywords: Bioenergy; Biomass; Collagen; Fishery residues